THE RELATIONSHIP BETWEEN SELF-EFFICACY AND LECTURER’S ASSERTIVE BEHAVIOR WITH FOREIGN LANGUAGE ANXIETY - Surya, Dedy; Menanti, Asih; Siregar, Nina Siti Salmaniah (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2018)
This quantitative research aimed to determine the relationship between self-efficacy and lecturer?s assertive behavior with foreign language anxiety experienced by university student. The population in this study was the students of the Department of English Education, State Institute for Islamic Studies Langsa. The samples were selected by using Stratified Random Sampling technique and sorted 147 students in semester 2, 4, and 6 that spread proportionally. The data were collected by using Foreign Language Classroom Anxiety Scale (FLCAS), self-efficacy scale, and lecturer?s assertive behavior scale. The data, then, were analyzed by multivariate linear regression. The result showed that self-efficacy and lecturer?s assertive behavior significantly contributed to foreign language anxiety. The effective contribution of self-efficacy and lecturer?s assertive behavior to foreign language anxiety was 58,4%.